2018
DOI: 10.1002/ijgo.12496
|View full text |Cite
|
Sign up to set email alerts
|

Impact of introducing specific measures to reduce the frequency of cesarean delivery for non‐obstetric indications

Abstract: The frequency of cesarean delivery for non-obstetric indications was reduced significantly by introducing specific reasonable measures. These included all non-obstetric indications for cesarean delivery being approved by a leading specialist of the related department, close cooperation with professionals from other specialties, and, additionally, staff attending professional educational lectures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…A large portion of these indications was neurological (mainly disc protrusion) and orthopedic (status post luxationem coxae congenita). This trend was previously reported by the study group 13 and concurs with Kacerauskiene et al 20 who observed a decrease in CS performed for non‐obstetric indications in primiparous women in selected hospitals in Lithuania from 2.6% to 1.5%, after the implementation of specific measures by the Lithuanian obstetrics specialty society. This highlights the impact other specialties might have on a unit’s rate of CS and the importance of multidisciplinary involvement in training for any successful intervention to improve maternity outcomes.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A large portion of these indications was neurological (mainly disc protrusion) and orthopedic (status post luxationem coxae congenita). This trend was previously reported by the study group 13 and concurs with Kacerauskiene et al 20 who observed a decrease in CS performed for non‐obstetric indications in primiparous women in selected hospitals in Lithuania from 2.6% to 1.5%, after the implementation of specific measures by the Lithuanian obstetrics specialty society. This highlights the impact other specialties might have on a unit’s rate of CS and the importance of multidisciplinary involvement in training for any successful intervention to improve maternity outcomes.…”
Section: Discussionsupporting
confidence: 90%
“…Staff training: Retraining maternity medical staff in the interpretation and management of intrapartum CTG in line with recommendations from the International Federation of Gynecology and Obstetrics (FIGO) 12 . Between January and June 2017, the senior consultant of the intrapartum care team and lead of the labor unit organized a series of lectures to all medical staff on interpretation of CTG and ran regular interactive sessions to discuss the management of controversial cases. Organizing evidence‐based lectures for non‐maternity medical staff about non‐obstetrical indications for CS 13 . In February 2017, the head of department organized a hospital wide lecture on the topic of “Non‐obstetric indications for cesarean section based on new evidence‐based medicine findings.” Subsequently, a guideline covering the same topic was developed and accepted, based on which only the lead doctor for that deprtament (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…In this regard, one of the important measures is the audit of own results using the Robson classification of mothers [11]. Our team has been dealing with the analysis of indications of caesarean sections and the possibility of influencing their development for a long time, which has led to a gradual decrease in the frequency of elective as well as acute sections [8,12,13]. We expected that anti-pandemic measures, especially the reduction of the presence of partner and doula during childbirth as well as the restriction of private births for doctors and midwives, will increase the frequency of caesarean sections, mainly due to indications of dysfunctional birth, because their presence favourably affects the course of childbirth [14].…”
Section: Discussionmentioning
confidence: 99%
“…Psenkova et al [11] showed that number cesarean operations with non-obstetric indications significantly reduced after training of obstetricians on non-obstetric cesarean section indications. These data reported in the literature indicate that more studies are required on the issue of how the ophthalmologic diseases affect the mode of delivery, and training on this issue is required for the relevant specialty areas.…”
Section: Discussionmentioning
confidence: 99%